An experimental investigation on the airside performance of fin-and-tube heat exchangers having corrugated louver fins - Part I; dry surface - Nae-Hyun KIM (Journal of Thermal Science and Technology, 2020)
Corrugated louver fin, which has louvers on wavy surface, may be a promising mean to augment the air-side heat transfer of fin-and-tube heat exchangers. However, only limited prior studies are available. In this study, two kinds of corrugated louver fin-and-tube heat exchangers – one having one corrugation per row and the other having two corrugations per row – were tested, and the results were compared with those of the standard louver fin and the plain fin samples. The highest j and f factor were obtained for the standard louver fin sample, followed by the single corrugated louver fin, the double corrugated inclined louver fin and then the plain fin sample. The high j and f factor of the standard louver fin sample may be due to the large louver fraction on the fin surface. Furthermore, larger fin surface area of the double corrugated louver fin compared with that of the single corrugated fin may be the reason for the smaller j and f factor. All the enhanced fin samples yielded larger heat transfer capacity than the plain fin sample at the same pumping power. Furthermore, the largest heat transfer capacity per pumping power was obtained for the standard louver fin sample. The single corrugated louver fin sample yielded higher heat transfer capacity per pumping power than the double corrugated sample.